Goldmann applanation tonometry - Lewis, Richard A.; American Academy of Ophthalmology (San Francisco : American Academy of Ophthalmology, 1988)
Topics covered : positioning the patient, slit lamp usage, asministering drops, measuring intraocular pressure and cleaning the applanating tip.
Keywords: Tonometry -- methods -- videocassettes